Gamma-oryzanol: a novel promising supplement for diabetes mellitus - Radda, Mustapha Ismail; Omar, Norsuhana; Ahmad, Rozaziana; Jalil, Rohana Abdul; Ishak, Wan Rosli Wan; Zin, Anani Aila Mat; Romli, Aminah Che (Faculty of Medicine, Universitas Trisakti, 2025)
The global prevalence of diabetes is rising at an alarming rate, with nearly 11% of adults currently affected. Projections estimate that by 2045, approximately 800 million individuals—1 in every 8 people—will have diabetes, representing a 46% increase in cases. Effective dietary management, however, offers the potential to delay or reduce diabetes-related complications. Gamma-oryzanol (γ-ORZ), a bioactive compound in brown rice (BR), has shown promising effects on type 2 diabetes mellitus (T2DM) and its complications, as evidenced by various scientific studies. Despite its potential, γ-ORZ's mechanisms of action remain underexplored, and BR consumption is less prevalent compared to white rice (WR). This review aimed to examine the effects of γ-ORZ on diabetes, promoting further research and encouraging the adoption of BR in dietary practices. Relevant studies were identified through a systematic search of PubMed, ScienceDirect, and Google Scholar for articles published between January 2013 and December 2023 using the keywords “(Gamma-oryzanol OR γ-oryzanol OR γ-ORZ) AND (Diabetes Mellitus OR Type-2 diabetes mellitus OR T2DM OR Hyperglycemia OR Insulin Resistance).” From an initial pool of 1,912 articles, 15 studies meeting the inclusion criteria were reviewed. Findings revealed that γ-ORZ exhibits antihyperglycemic, antidyslipidemic, anti-inflammatory, and antioxidant properties. It mitigates β-cell dysfunction, improves adipocyte function, enhances insulin secretion and sensitivity, and alleviates diabetic cardiomyopathy. This review underscores γ-ORZ's therapeutic potential in managing diabetes and its complications, while highlighting the need for more robust studies to validate its efficacy and compare it with standard treatments.